Perilaku Bertanggungjawab Lingkungan Siswa (Hubungan Antara Pengetahuan Tentang Perubahan Iklim Dan Self Efficacy dengan Perilaku Bertanggungjawab Lingkungan Siswa) - PRETTY M. SIMANJUNTAK (IJEEM - Indonesian Journal of Environmental Education and Management, 2016)
The aim of this research is o find out the (1) Relationship between knowledge about climate changes and responsible environmental behaviour; (2) Relationship between self efficacy and responsible environmental behaviour; (3) Relationship both of knowledge about climate changes and self efficacy with responsible environmental behaviour. The research usedquantitative methods with correlation approach. The research used samples 116 students in Sinar Dharma Senior High School. Data were collected through participant observation using the instrument with quesioner.The results of the research reveal that(1) There is a positive relationship between knowledge about climate changes and responsible environmental behaviou; (2) There is a positive relationship between self efficacy and responsible environmental behaviour; (3) There is a positive relationshipboth of knowledge about climate changes and self efficacy with responsible environmental behaviour.According the result of his research, knowledge about climate changes and self efficacy are importan to improve responsible environmental behaviour.